The Berenstain Bears and the big date - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1998)
Brother Bear experiences jealousy when his friend Bonnie agrees to go out on a date with the rich and spoiled Ronnie Grizzington III.
Keywords: Jealousy -- Fiction; Wealth -- Fiction; Bears -- Fiction